Design and Investigation of Frequency Selective Surface Loaded Thermoplastic Polyurethane Polymer-Based 5G Absorber - Agrawal A.; Kumar A.; Panwar R. (My University, 2025)
In the past few years, numerous efforts have been undertaken towards the development of microwave absorbers that are simple, broadband, angularly stable, lightweight, conformal, and unaffected by polarization effects. This work comprises a single-layer decagonal ring-shaped frequency selective surface (FSS) loaded thermoplastic polyurethane polymer-based absorber for the mm-wave band. The designed absorber with a dielectric substrate having a thickness of only 1.7 mm achieves a -10 dB reflection coefficient (RC) bandwidth of 5.5 GHz (23-28.5 GHz) for the normal angle of incidence. Furthermore, the proposed absorber shows a minimum RC of -28 dB at 26 GHz centre or resonant frequency. Moreover, the surface current distributions at a resonant frequency of the proposed microwave absorber are also investigated. The presented absorber is lightweight, flexible, polarization insensitive, angularly stable, and suitable for 5G applications. © 2023 IEEE.